SISTEM CERDAS PERHITUNGAN JASA PERBANKAN BERBASIS DESKTOP - Ita Dewi Sintawati; Giri Wahyu Prasetyo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The complexity of bank interest calculations and the many types of banking services make some people reluctant to do bank interest calculations independently. The application of technology in calculating interest rates is necessary to avoid calculation errors and facilitate making decision because many people do not know for sure about calculating bank interest rates. The calculation of banking services in this application is limited to a limited scope, which is only limited to the calculation of deposits, loans and building collateral. The banking services application is created using visual studio 2010 software with visual basic.net programming language. The interest calculation formula is obtained through various references, in the calculation of banking service applications it is not related to any bank data, so the input parameters are parameters determined by the user and then processed by the application to be output. Application of banking services becomes an alternative means to calculate computerized deposits, loans and building collateral so that it is faster and reduces the error rate when calculated manually with a calculator.